Physical activity measured by accelerometry among adolescents participating in sports clubs and non-participating peers - Toivo K; Vähä-Ypyä H; Kannus P; Tokola K; Alanko L; Heinonen OJ; Korpelainen R; Parkkari J; Savonen K; Selänne H; Kokko S; Kujala UM; et al. (TAYLOR & FRANCIS LTD, 2022)
The purpose of this descriptive cross-sectional study is to describe the amount and intensity of physical activity (PA) measured by accelerometry among adolescents participating in organized sports (SCP) and age-matched non-participating peers (NP). SCPs (332) and NPs (139) wore an accelerometer on the hip for seven days. PA was reported using the 1-min exponential moving average. The current moderate-to-vigorous physical activity (MVPA) recommendation of at least an average of 60 min of MVPA daily was reached by 85% of SCPs and 45% of NPs (p < .001). During training days, the MVPA times among SCPs ranged from 153 ± 39 min in males and 109 ± 35 min in females participating in basketball to 113 ± 33 min in males participating in floorball and 83 ± 32 min in females participating in gymnastics. Sports participation contributes rather strongly to the accumulation of the recommended amount of MVPA. During training days, SCPs, except for females participating in gymnastics, accumulated more MVPA than NPs. During non-training days, only males participating in cross-country skiing and females participating in track and field accumulated more MVPA than NPs.
PA of Finnish adolescents participating in nine different organized sports and age-matched non-participating peers was measured by accelerometry for one week and the results are reported using the 1-min exponential moving average.
Adolescents participating in many organized sports accumulated more PA than non-participants; this was observed in meeting the PA recommendations, total amount of PA at different intensities, and step count.
The current PA recommendation of at least an average of 60 min of MVPA per day was reached by 85% of SCPs and 45% of non-participating peers. Vigorous physical activity at least three times per week was incorporated by 96% of SCPs and 81% of NPs.
During training days, males participating in soccer, basketball, and cross-country skiing spent more time in MVPA than females participating in the same sports. During non-training days, the time spent in MVPA was similar between males and females participating in sports clubs.